Langerhans cell histiocytosis in a child with a perianal skin lesion and constipation. - Valletta, E.; Fornaro, M.; Schena, D.; Colato, C.; Zaccaron, A.; Camoglio, F.S. (European Journal of Pediatric Dermatology, 2008)
A 26-month-old boy was referred to the Pediatric Gastroenterology Department due to perianal ulcerated lesions and worsening constipation from 6 months. A gastrointestinal disorder was hypothesized. However, the normal findings of the rectum and sigma mucosa and mainly the histological examination of the skin led to diagnose Langerhans cell histiocytosis with skin and bone involvement. The disease responded to the treatment with vinblastine and prednisone.